(3CfjS GdeLJgOjfs - (3GdfQGbj GdcGTGfj, egOj Hf CHj PQ, J (B1209 (3g`s ((3MSjf Hf ejQ SjO Ydj GdLGSjs)
(3ChdgG (B:s
(3aUd ; GdMb Gf GdhGh GdYGWaI deWdb GdLeY hdG jOd Ydi JQJjH Ch (B.. (3UQM HPdc QDSGA GddZI MJi Cf CHG Ydi GdaGQSj fbd ELeGY GdCOHGA Ydi Pdc hPcQg SjHhjg aj NeSI YTQ ehVYG (B...s
(3BNQgG (B:s
... (3dCf GdYeOI Cj GdYdI acdeG cGf GdJTGHg ajgeG CcKQ cGf Cbhi hZjQ Naj Cf HYV gPg GdJQLjMGJ jJCJi Ydi eG PgHfG Edjg ceG YQaJ hGdHhGbj eJQhcI YfOfG (B.. (3hHYO GdEMGWI HeG PcQfGg dGjNai LdjJg GdMGd ajg (B. (3bO aQZJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\313s
(3GdPQjYI (B2\1804s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs